Periodontal and microbial responses of obese individuals after short term non-surgical periodontal therapy / Khairunnisa Md Tahir - Khairunnisa, Md Tahir (2017)
The association between obesity and chronic periodontitis has been well documented. However, the response of obesity on periodontal and microbial following non–surgical periodontal therapy (NSPT) remains unclear. Thus, this study is aimed to investigate the response of obesity on the clinical parameters and periodontal pathogens profile following short term of NSPT. The study also assessed the correlation between clinical parameters and periodontal pathogens profile. This prospective study involved 30 obese (test group) and 30 non–obese (control group). Obese is defined as individual who have BMI ≥ 30.0 kg/m2 . Ethical approval was obtained (DF PE1501/0085(L)). The clinical parameters (visible plaque index (VPI), gingival bleeding index (GBI), probing pocket depth (PPD) and clinical attachment loss (CAL)) were obtained from the Malaysian Periodontal Database and Biobank Database (MPDBS). The subgingival plaques samples were collected at baseline and at 12 weeks following NSPT by previous researchers. Quantitative real–time polymerase chain reaction (qPCR) was used to quantify the mean count of periodontal pathogens. The obese group showed greater reduction in mean differences of VPI and GBI (69% and 53%) at 12 weeks post NSPT compared to the non–obese group (15% and 15%) respectively. After adjusting the confounding factors, the obese group was found as a potential associated (p < 0.0001) factor in mean changes of VPI and GBI. Following NSPT, means PPD and CAL in both groups was significantly reduced after 12 weeks except for CAL in the non–obese groups. In terms of periodontal pathogens profile, the obese group showed significant reduction only on P. intermedia (up to 49%) compared with reduction means count of P. gingivalis, T. forsythia and A. actinomycetemcomitans (up to 100%) in the non–obese group. No correlation was found between the clinical parameters and periodontal pathogens profiles in the obese groups with chronic periodontitis following 12 weeks v NSPT. From the findings, it can be summarized that the obese group showed higher VPI and GBI but lower PPD and CAL compared to the non–obese group following 12 weeks NSPT. Furthermore, lower P. gingivalis and T. forsythia but higher P. intermedia were observed in the obese group at 12 weeks post NSPT. No correlation was found between clinical parameters and periodontal pathogens profile in the obese group.